Vitamin D in Human Health - Maja Šikić Pogačar; Dušanka Mičetić-Turk (Acta Medico-Biotechnica, 2021)
The generic term vitamin D designates a group of chemically related compounds that possess antirachitic activity. Today, the definition of optimal level of vitamin D is based on serum concentrations of 25–hydroxyvitamin D [25(OH)D]. It can be introduced into the organism through ingested food (especially oily fish, milk, with enrichment food and food supplements), or can be dermally synthesized by exposure of the skin to sunlight. Vitamin D deficiency in the past was defined by the clinical recognition of nutritional rickets, a disease nearly eradicated by vitamin D fortification. In addition to its well–recognised role in musculoskeletal health, over the last decade evidence has suggested that low serum concentrations of 25–hydroxyvitamin D, 25(OH)D, are associated with a number of non–skeletal disorders including heart disease, immune and metabolic diseases as well as age–related cognitive decline and cancer. For that reason, there has been a renewed interest in the nutrient vitamin D. Despite its important role in the health, The generic term vitamin D designates a group of chemically related compounds that possess antirachitic activity. Today, the definition of optimal level of vitamin D is based on serum concentrations of 25–hydroxyvitamin D [25(OH)D]. It can be introduced into the organism through ingested food (especially oily fish, milk, with enrichment food and food supplements), or can be dermally synthesized by exposure of the skin to sunlight. Vitamin D deficiency in the past was defined by the clinical recognition of nutritional rickets, a disease nearly eradicated by vitamin D fortification. In addition to its well–recognised role in musculoskeletal health, over the last decade evidence has suggested that low serum concentrations of 25–hydroxyvitamin D, 25(OH)D, are associated with a number of non–skeletal disorders including heart disease, immune and metabolic diseases as well as age–related cognitive decline and cancer. For that reason, there has been a renewed interest in the nutrient vitamin D.